(Mono-) Exposure to Naphthalene in the Abrasives Industry: Air Monitoring and Biological Monitoring. Issue 9 (13th July 2020) - Weiss, Tobias; Breuer, Dietmar; Bury, Daniel; Friedrich, Claudia; Werner, Silke; Aziz, Mohammed; Hummel, Thomas; Raulf, Monika; Zschiesche, Wolfgang; Sucker, Kirsten; Pallapies, Dirk; Bünger, Jürgen; et al.
Abstract: Exposure to the bicyclic aromatic hydrocarbon naphthalene occurs in most cases along with other polycyclic aromatic hydrocarbons. Here we report from an investigation of 63 healthy, non-smoking male employees in the abrasives industry where naphthalene is the only relevant chemical exposure. Exposure assessment was performed using a combination of Air and Biological Monitoring over nearly a whole working week (Mo.–Th.). Air measurements were carried out during the shift on Thursday with the GGP mini-sampling system, combining particle and vapour sampling at low flow rates. In urine spot samples, the metabolites 1- and 2-naphthol were measured Mo.–Th. pre- and post-shift (for the reference group only Mo. pre- and Th. post-shift). With regard to naphthalene concentrations measured in air and concentrations of its metabolites (1- and 2-naphthol) in urine, study participants could be divided into a high and a low exposure group, and a reference group. The naphthalene concentration in air was in the range of 0.1–11.6 mg m −3, and naphthol concentrations (sum of 1- and 2-naphthol) in post-shift urine were in the range of <1 to 10 127 µg l −1 . Naphthalene concentrations in air and naphthol concentrations in urine were closely correlated, indicating mainly airborne exposure at the investigated workplaces. As expected from toxicokinetic data, internal body burden increased slightly during a working week and did not completely decline over a work-free weekend to background concentrations observed in occupationally not exposed persons. Taking into account the observed increase in pre- and post-shift values during the working week, urine sampling for Biological Monitoring at workplaces should be carried out after several preceding shifts. Our data allow the derivation of biological limit values for the sum of 1- and 2-naphthol in urine corresponding to occupational exposure limits for naphthalene in air.